Digital Controlled Hydraulic Drives of Working Machines - Płonecki, L.; Cendrowicz, J. (Engineering Transactions, 1993)
The paper is aimed at discussing the monitored control systems with different regulation algorithms, exemplified by a linear hydraulic drive. Results of experiments concerning the drives of a single bucket hydraulic digger are presented in order to compare the regulation quality in the cases discussed.